Identifikasi Kadar Gula Darah pada Atlet Angkat Besi Menggunakan Aplikasi Berbasis WEB - Simanjuntak, Norma Rotua; Sitompul, Akhirul Jumaisal; Agraini, Agraini; Inderiati, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze blood sugar levels in weightlifters in Jambi City using a web-based application. The method used is descriptive observational using a survey design. The research results showed that normal blood sugar levels were greater than abnormal blood sugar levels based on gender and age. In conclusion, blood sugar levels in weightlifting athletes are predominantly normal based on age and gender. Keywords: Weightlifting Athletes, Blood Glucose Levels, Web